Credit rationing, courts, property rights and public debt - Gallardo Del ANgel, Roberto; Xu, Yiwen (Revista Mexicana de Economía y Finanzas Nueva Época REMEF, 2023)
This work presents a model of credit rationing under the effect of judiciary inefficiency and lack of protection of property rights. We study the credit contracts when deficient judicial performance interacts with lack of property rights protection. The results shows that bank credit will be rationed when judicial efficiency and property rights protection are defficient. Banks are negatively affected by judicial inefficiency because they observe that they cannot be granted by courts of their entire repayment in the case of default.Entrepreneurs are willing to offer less collateral and Banks will demand higher collateral and projects with better returns. In our analysis, while some entrepreneurs are rationed, banks may nd safer to lend the rationed credit to public institutions and the Government in general. But in this scenario of poor institutional quality, the Government might be induced to keep low institutional quality in order to that have available credit from Banks. But this low institutional quality might let the level of public debt to explode until it became unmanageable over time, threatening the macroeconomic stability.